INTEGRATIVE TAXONOMY REVEALS CRYPTIC ROBIN LINEAGE IN THE GREATER SUNDA ISLANDS - Elize Y. X. Ng; Arya Y. Yue; James A. Eaton; Chyi Yin Gwee; Bas van Balen; Frank E. Rheindt (Treubia, 2020)
Southeast Asian avifauna is under threat from both habitat loss and illegal poaching, yet the region’s rich biodiversity remains understudied. Here, we uncover cryptic species-level diversity in the Sunda Blue Robin (Myiomela diana), a songbird complex endemic to Javan (subspecies diana) and Sumatran (subspecies sumatrana) mountains. Taxonomic inquiry into these populations has previously been hampered by a lack of DNA material and the birds’ general scarcity, especially sumatrana which is only known from few localities. We demonstrate fundamental bioacoustic differences in courtship song paired with important distinctions in plumage saturation and tail length that combine to suggest species-level treatment for the two taxa. Treated separately, both taxa are independently threatened by illegal poaching and habitat loss, and demand conservation action. Our study highlights a case of underestimated avifaunal diversity that is in urgent need of revision in the face of imminent threats to species survival.